Investigaciones Feministas 2014, vol. 5 207-231 208 Development and crisis of reconciliation of work and family life policies in Spain (1997-2014). An explanatory framework - Campillo, Ines (Investigaciones Feministas (Feminist Research), 2015)
In recent years, the analysis of the factors that have pushed the transformation of post-industrial welfare states has become a central research agenda for welfare state scholars. Different analysis of social policies' changes have underlined the explanatory power of one or some of the following factors: the pressure of globalization, the impact of the European Union, the appearance of “new social risks” associated to the socioeconomic and demographic transformations of the last decades, the power resources of leftist organizations, and the influence of the political and institutional arrangements and legacies. Mainstream researchers have usually tested their hypotheses in the sectors of social policy that are considered central, such as pensions or health services. However, these hypotheses have been rarely examined in the case of family policies, which paradoxically constitute the sector of social policy that has suffered the greatest changes in recent years.The present paper tackles this lacuna through an analysis of the causes that pushed the development – and subsequent decline- of reconciliation policies in Spain from 1997 to 2014. To that aim, I present a “pluralist” framework for the study of social policy transformations and, in particular, for the study of reconciliation policy transformations. Against the predominance of institutionalist explanations in this field, I recover the power resources theory and propose a feminist reformulation. Thus, I contend that the key to understanding the development –and subsequent decline– or reconciliation of work and family life policies in Spain is the interaction between the economic situation and women’s power resources, factors that in turn interact with other variables such as the new social risks, the influence of the European Union and the institutional legacy.
Keywords: Welfare state transformations; reconciliation of work and family life policies; economic situation; women’s power resources